2020
DOI: 10.1002/bdr2.1714
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional folic acid supplement use among women of reproductive age and its determinants in central rural Germany: Results from a cross sectional study

Abstract: BackgroundPrevalence of neural tube defects (NTD) has not decreased in Germany despite longstanding recommendations for folic acid supplementation. To examine the prevalence of periconceptional folic acid supplement use and associated factors among German women of reproductive age.MethodsCross‐sectional survey was conducted in hospital‐based maternity units in rural Germany. A sample of 1,004 women of reproductive age, either pregnant or in their early postpartum period, took interviewer/self‐administered pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The absence of knowledge of FAS, the reluctance to take many tablets and pills during pregnancy, or beliefs that a balanced diet can prevent low folate levels, could be better tackled with folate fortification rather than relying on the women's initiative to take tablets. Food fortification, whose German advocates are relentlessly calling for (4,7) , remains despite some shortcomings (e.g. vitamin B 12 masking (35) ) the most successful and most equitable intervention to tackle folate deficiency (36) , while behavioural interventions to increase individual supplementation are proven ineffective or poorly documented (37) .…”
Section: Main Implications Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of knowledge of FAS, the reluctance to take many tablets and pills during pregnancy, or beliefs that a balanced diet can prevent low folate levels, could be better tackled with folate fortification rather than relying on the women's initiative to take tablets. Food fortification, whose German advocates are relentlessly calling for (4,7) , remains despite some shortcomings (e.g. vitamin B 12 masking (35) ) the most successful and most equitable intervention to tackle folate deficiency (36) , while behavioural interventions to increase individual supplementation are proven ineffective or poorly documented (37) .…”
Section: Main Implications Of the Resultsmentioning
confidence: 99%
“…A smaller but more recent study conducted in 2009 in the Munich area found that 85•6 % of pregnant women had taken supplement during or before their pregnancy (and 33•7 % before) (6) . Even more recently, a crosssectional study conducted in rural Germany estimated the prevalence of FAS during the whole of the periconceptional phase at 41•5 % (7) .…”
mentioning
confidence: 99%
“…Similarly, a study found that 41.5% of their study samples took FA during the preconception period while 47.4% took it during pregnancy [ 19 ]. This result was found to be associated with the education level, planning for pregnancy, and the pregnancy experience.…”
Section: Discussionmentioning
confidence: 99%
“…Family planning is therefore of high importance when discussing health awareness among pregnant women. The targeted promotion of folic acid supplement use should be conducted periodically by gynecologists and primary care physicians during annual medical screenings [37].…”
Section: Discussionmentioning
confidence: 99%